Engine design using rapid prototyping techniques - Martins, Jorge (2005)
An internal combustion engine was designed in ProEngineer. The aim of this project was to develop a proposefull tool enabling the rapid design/development of the required engine. The first non-working model was built using a rapid prototyping machine. A visual analysis of the engine head model shown various fields where improvements could be made on the engine design. Therefore, the head was re-designed taking that into account. The second phase of the project involves the actual production of low cost direct casting moulds straight from the engine design. Design and manufacture integration now possible through Rapid Prototyping techniques enabled drastic reductions of the design-development-casting process effort.